2021
DOI: 10.3390/heritage4030130
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Embrittlement of Ancient Copper and Silver Alloys

Abstract: The manifestations of ancient metals’ embrittlement, cracking and fracture, are challenging problems for restorers and conservators, yet the scientific understanding of these problems is limited. In particular, the study and interpretation of fracture surfaces, fractography, is a minor or non-existent consideration for most archaeometallurgical investigations. This paper presents a survey of fractographic analyses, in combination with the more widely used disciplines of microstructural studies, metallography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…The average concentrations of silver and copper in each coin are very close to each other and, respectively, around 98.45% for silver and around 1.15% for copper. Several studies have shown that copper contents above 0.5-1 wt.% indicate deliberate additions, most probably to increase the strength and wear resistance in high-silver alloys, and also in larger amounts to make lower-quality artifacts and coins [13]. In this study, copper was detected above the range.…”
Section: Discussionsupporting
confidence: 46%
“…The average concentrations of silver and copper in each coin are very close to each other and, respectively, around 98.45% for silver and around 1.15% for copper. Several studies have shown that copper contents above 0.5-1 wt.% indicate deliberate additions, most probably to increase the strength and wear resistance in high-silver alloys, and also in larger amounts to make lower-quality artifacts and coins [13]. In this study, copper was detected above the range.…”
Section: Discussionsupporting
confidence: 46%
“…In general, the patinas can be classified into two main types: those that preserve the demarcation with the original surface and those that instead corrode and break up the profile of the product. Simplified examples of this subdivision are reported in the literature [19][20][21][22]. Patinas resulting from redox processes are attributable to the first type; crusts and patinas are also generated by acid-base reactions related to the second in which moisture flows play a central role in the transport of ions (i.e., mainly through hydrolysis and ionic exchange), while a third type includes those deriving from processes of site contamination (diffusion, segregation, deposition, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Ancient silver was commonly produced from silver-rich galena lead sulfide ore using the cupellation process [ 10 ]. The presence of Pb and S in some of the measurements is thus probably related to the cupellation process [ 11 , 21 ]. The cupellation technique is very effective for the production of high-purity silver metal, with more than 95 wt% Ag [ 11 ], which may explain the high purity of the discussed Yehud silver coins.…”
Section: Discussionmentioning
confidence: 99%
“…In the third hearth, several globules were melted and refined to obtain silver ingots and the remaining lead oxide was absorbed in the porous container wall (cupel). The cupellation method is a very effective process for producing silver metal with more than 95% purity [ 11 ].…”
Section: Technological Background To Researchmentioning
confidence: 99%